Pengaruh Sistem Peredupan terhadap Efisiensi Energi Penerangan Jalan Umum pada Universitas Indonesia Berdasarkan Metode Lumen - Muhammad Arkhan Pradanugraha; Budi Sudiarto (PROtek : Jurnal Ilmiah Teknik Elektro, 2022)
LEDs in lighting systems have been widely used, including public street lighting systems. However, the selection of public street lights in Indonesia often does not use lumen calculations and light dimming technology. This study aims to improve energy consumption efficiency by replacing existing lamps with LED lamps according to the lumen calculation method and using a smart system in the form of automatic dimming of the lamps. The research study was carried out in two stages: the measurement of illumination using a lux meter and the analysis of energy consumption between the existing and the replacement. The replacement scenario is to replace the existing lamps with LED lamps equipped with an automatic dimming system based on lumen calculations. The lighting level is adjusted to Indonesian lighting standards, SNI 7391:2008, 2 to 5 lux. The result of the study is that carrying out a replacement scenario can increase energy consumption efficiency by 77.95%.